Scaffold attachment factor B: distribution and interaction with ERα in the rat brain. - Hashimoto, Takashi; Kawata, Mitsuhiro; Hirahara, Yukie; Nishi, Mayumi; Satoshi, Iino; Matsuda, Ken-Ichi (Histochemistry & Cell Biology, 2020)
Scaffold attachment factor (SAFB) 1 and its homologue SAFB2 are multifunctional proteins that are involved in various cellular mechanisms, including chromatin organization and transcriptional regulation, and are also corepressors of estrogen receptor alpha (ERα). Both SAFBs are expressed at high levels in the brain. However, the distributions of SAFB1 and SAFB2 have yet to be characterized in detail and it is unclear whether both proteins interact with ERα in the brain. In this study, we investigated the expression and distribution of both SAFBs and their interaction with ERα in adult male rat brain. Immunohistochemical staining showed that SAFB1 and SAFB2 have a similar distribution pattern and are widely expressed throughout the brain. Double-fluorescence immunohistochemical and immunocytochemical analyses in primary cultures showed that the two SAFB proteins are localized in nuclei of neurons, astrocytes, and oligodendrocytes. Of note, SAFB2 was also found in cytoplasmic regions in these cell lineages. Both SAFB proteins were also expressed in ERα-positive cells in the medial preoptic area (MPOA) and arcuate and ventromedial hypothalamic nuclei. Co-immunoprecipitation experiments revealed that both SAFB proteins from the MPOA reciprocally interact with endogenous ERα. These results indicate that, in addition to a role in basal cellular function in the brain, the SAFB proteins may serve as ERα corepressors in hormone-sensitive regions.